IMPLEMENTASI DATA MINING PENJUALAN ALAT TULIS KANTOR PADA PT TERANG JAYA LESTARI MENGGUNAKAN ALOGARITMA APRIOR - Ragil, Ragil Wijianto; mulyawan, Antony (Informatics and Computer Engineering Journal, 2022)
Stationery has indeed become a very important and much sought after requirement, especially forschool children and office employees. In this study, the authors perform data processing on ATK sales to classifyATK data and look for accuracy values as a determination of what goods are most in demand by customers. Thepurpose of this research is as a marketing strategy in order to optimize the company's work in processingavailable stock data so that it can meet customer needs. To find out the type of ATK that consumers are mostinterested in, it takes a Data Mining technique with the Apriori Algorithm method and is supported by theTanagra application by researching sales data for 1 year. Data Mining is a combination of data analysistechniques, while the Apriori Algorithm is the method most often used because it is very simple, easy and themost widely proposed by several researchers, because there are parameters, namely Support Value (Support)and Confidence Value (Confidence). Then the results of the research predictions obtained, that the sales ofstationery that are most in demand by customers are Kepper Documents, Map L, and Business Files